Ancestral Norms, Legal Origins, and Female Empowerment - Abel Brodeur; Marie Christelle Mabeu; Roland Pongou (Institute of Labor Economics (IZA), 2020)
A large literature documents persistent impacts of formal historical institutions. However, very little is known about how these institutions interact with ancestral traditions to determine long-term economic and social outcomes. This paper addresses this question by studying the persistent effect of legal origins on female economic empowerment in sub-Saharan Africa, and how ancestral cultural norms of gender roles may attenuate or exacerbate this effect. Taking advantage of the arbitrary division of ancestral ethnic homelands across countries with different legal origins, we directly compare women among the same ethnic group living in civil law countries and common law countries. We find that, on average, women in common law countries are signicantly more educated, are more likely to work in the professional sector, and are less likely to marry at young age. However, these effects are either absent or significantly lower in settings where ancestral cultural norms do not promote women's rights and empowerment. In particular, we find little effect in bride price societies, patrilocal societies, and societies where women were not involved in agriculture in the past. Our findings imply that to be optimal, the design of formal institutions should account for ancestral traditions.
Keywords: D03; I25; J16; N37; 330; legal origins; ancestral norms; women's empowerment; gender roles